The Contribution of the Islamic Civilization Course to the Islamic Insight of Sharia Accounting Students at Sunan Kalijaga State Islamic University - Wardhani, Nanda Kusuma (Universitas Islam Negeri Sumatera Utara, 2024)
Islamic Civilization is one of the courses taught in the Sharia Accounting study program. The objectives of this study are to determine the contribution of Islamic civilization courses in providing in-depth understanding and its contribution to the Islamic insights of Islamic Accounting students. This study used a qualitative approach with a case study method. The results of this research indicated that the Islamic civilization course provided a significant contribution to the Islamic insight of Sharia Accounting students. Through this course, students gain an understanding of the history and development of Islamic civilization, the values contained therein, and the contributions of Islamic Civilization in various fields of life from time to time. With the understanding that has been obtained, students can become more competent and qualified and have a high awareness of Islamic values.